Wear-resistant puncture-proof butyronitrile glove and preparation method thereof

Through the preparation of composite latex and synergistic fiber, the problems of insufficient anti-static, wear resistance and puncture resistance of nitrile gloves have been solved, the wear resistance, puncture resistance, anti-static and antibacterial properties of gloves have been significantly improved, and their application range has been expanded.

CN120737458AActive Publication Date: 2025-10-03ANQING YINGKE MEDICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511220059.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-10-03
Estimated Expiration
2045-08-29

AI Technical Summary

Technical Problem

Existing nitrile gloves have poor anti-static properties, wear resistance and puncture resistance, which limits their application.

Method used

Composite latex is used to prepare wear-resistant and puncture-resistant nitrile gloves. Hard particles such as nanodiamonds and nanoalumina in the synergistic fibers resist wear and puncture. The basalt fiber reinforced skeleton bears friction stress. Carboxylated single-walled carbon nanotubes and graphene form a lubricating and barrier effect. The electrospinning layer and coating layer improve conductivity and antibacterial properties.

Benefits of technology

It significantly improves the wear resistance, puncture resistance, anti-static and antibacterial properties of nitrile gloves, and enhances their mechanical stability at low temperatures and wide application.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a wear-resistant puncture-proof butyronitrile glove and a preparation method thereof, and relates to the technical field of butyronitrile gloves. The butyronitrile glove is prepared from a composite adhesive emulsion. The composite adhesive emulsion is prepared from the following raw materials in parts by mass: 80 to 90 parts of carboxylic butadiene-acrylonitrile latex, 13 to 18 parts of mixed dispersion liquid, 0.5 to 1.1 parts of anti-aging agent RD, 6 to 12 parts of accelerant solution and 6 to 8 parts of synergistic fiber. The preparation method comprises the following steps: firstly, carrying out plasma treatment on etched basalt fibers, then carrying out electrostatic spinning wrapping by using a spinning solution containing carboxylated single-walled carbon nanotubes, nano-diamond and butyronitrile latex, and then carrying out wrapping by using a solution containing waterborne polyurethane, chitosan quaternary ammonium salt and graphene nanosheets; and finally, a coating containing nano aluminum oxide, carboxy nitrile rubber and a silane coupling agent is sprayed to prepare the synergistic fiber, so that the wear resistance, puncture resistance, antistatic property and antibacterial property of the butyronitrile gloves are effectively improved. Therefore, the method has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nitrile gloves, and in particular to wear-resistant and puncture-resistant nitrile gloves and a preparation method thereof. Background Art

[0002] Nitrile latex, made by emulsion polymerization of butadiene and acrylonitrile, exhibits excellent oil and chemical resistance and is widely used in the automotive, aviation, petroleum, and medical industries. Nitrile gloves are synthetic rubber protective gloves made primarily from nitrile rubber through processes such as dipping and molding. As synthetic materials, nitrile gloves do not contain the allergenic proteins found in natural latex, effectively preventing latex allergies. Furthermore, the acrylonitrile segments in the nitrile rubber molecular structure impart excellent oil and chemical resistance, while the butadiene segments provide excellent elasticity and flexibility, resulting in both tensile strength and a good fit. Consequently, nitrile gloves are widely used in healthcare, food processing, industrial operations, laboratory research, and other settings, primarily for hand protection, isolating hands from direct contact with contaminants, chemicals, and microorganisms, ensuring safe and hygienic operations.

[0003] However, in practical applications, nitrile gloves still suffer from poor anti-static properties. Excessive static electricity accumulation can cause breakdown of electronic components or sparks, as well as poor wear resistance and puncture resistance, which limits their application. Therefore, the anti-static, wear resistance, and puncture resistance of existing nitrile gloves still need to be further improved. Summary of the Invention

[0004] The purpose of the present invention is to provide a wear-resistant and puncture-resistant nitrile glove and a preparation method thereof, to solve the following technical problems: Existing nitrile gloves still have problems with poor anti-static properties, wear resistance, and puncture resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A wear-resistant and puncture-resistant nitrile glove, wherein the nitrile glove is made from a composite rubber latex; The composite latex comprises the following raw materials in parts by mass: 80-90 parts of carboxyl nitrile latex, 13-18 parts of mixed dispersion, 0.5-1.1 parts of antioxidant RD, 6-12 parts of accelerator solution, and 6-8 parts of synergistic fiber; The mixed dispersion is prepared from deionized water, sulfur, pigment, and sodium polycarboxylate; The synergistic fiber is prepared by electrostatically spinning basalt fibers with spinning solution after etching, and then sequentially coating with graphene nanosheets doped with polyurethane and nanoalumina doped with carboxylated nitrile rubber. The spinning solution includes carboxylated single-walled carbon nanotubes, sodium dodecylbenzenesulfonate, nano zinc oxide, nano diamond, γ-cyanopropyltrimethoxysilane, nitrile latex and polyvinyl pyrrolidone.

[0006] Preferably, the preparation method of the composite latex is as follows: The carboxyl nitrile latex is stirred at 50-70 r / min at 25-30° C. for 8-10 hours, and then the mixed dispersion, antioxidant RD, accelerator solution, and synergistic fiber are added in sequence while stirring, and the pH is adjusted to 8.5-9.5. After stirring for 2-4 hours, the mixture is matured at 25-30° C. for 8-10 hours to obtain a composite latex.

[0007] Preferably, the preparation method of the mixed dispersion is as follows: Add sulfur, pigment, and sodium polycarboxylate to deionized water and ball-mill until the D90 is 0.5-2 μm to obtain a mixed dispersion; The mass ratio of the deionized water, sulfur, pigment, and sodium polycarboxylate is 5-7:3-4:5-7:0.2-0.4; The pigment is a composition of titanium dioxide and any one of zinc oxide, phthalocyanine blue and pearlescent pigment.

[0008] Preferably, the preparation method of the accelerator solution is as follows: Add accelerator ZDBC and accelerator ZDEC to deionized water at 45-50°C and stir for 20-40 minutes to obtain an accelerator solution; The mass ratio of the deionized water, the accelerator ZDBC, and the accelerator ZDEC is 5.4-10.8:0.4-0.8:0.2-0.4.

[0009] Preferably, the preparation method of the synergistic fiber is as follows: A1: Add ammonium bifluoride and citric acid to deionized water and stir for 10-20 minutes. Then add basalt fiber and ultrasonically disperse it at 45-50°C for 30-50 minutes. Then, centrifuge and wash it with deionized water 5-7 times and dry it at 55-60°C to obtain etched fiber. A2: adding anhydrous ethanol, carboxylated single-walled carbon nanotubes, and sodium dodecylbenzenesulfonate to deionized water and ultrasonically dispersing them for 30-50 minutes, then adding nano-zinc oxide and nano-diamonds and ultrasonically dispersing them for 30-50 minutes, then adding γ-cyanopropyltrimethoxysilane and stirring at 55-60°C for 2-3 hours, and finally adding nitrile latex and polyvinyl pyrrolidone and stirring for 10-20 minutes to obtain a spinning solution; A3: Plasma treatment is performed on the etched fiber, followed by electrospinning with a spinning solution, followed by vacuum drying at 75-80°C for 1-2 hours to obtain a composite fiber; A4: Add waterborne polyurethane, chitosan quaternary ammonium salt, dioctyl terephthalate, and graphene nanosheets to deionized water, adjust the pH to 6.5-7.5, and heat at 2500-3000 rpm for 30-40 minutes. Then, immerse the composite fiber in the water, soak for 8-10 minutes, remove the water, and irradiate it. Finally, air dry it at 55-60°C for 1-2 hours to obtain the coated fiber. A5: Add silane coupling agent KH-560 and glacial acetic acid to deionized water and stir for 10-20 minutes. Then add nano-alumina and carboxyl nitrile rubber and stir at 2000-2200r / min for 20-30 minutes. After grinding, spray it on the surface of the coated fiber to form a coating with a thickness of 3-5μm. Then, irradiate it with infrared light, then keep it at 60-80℃ for 1-2 hours, and finally immerse it in silane coupling agent KH-570 ethanol solution for 10-15 minutes. After draining, dry it at 75-80℃ for 30-50 minutes to obtain synergistic fiber.

[0010] Preferably, the mass ratio of deionized water, ammonium bifluoride, citric acid, and basalt fiber in A1 is 100-120:5-6:3-3.5:20-25; The mass ratio of deionized water, anhydrous ethanol, carboxylated single-walled carbon nanotubes, sodium dodecylbenzenesulfonate, nano-zinc oxide, nano-diamond, γ-cyanopropyltrimethoxysilane, nitrile latex, and polyvinyl pyrrolidone in A2 is 30-45:30-45:1-1.5:0.05-0.07:3-4.5:2-3:0.18-0.28:5-7.5:0.2-0.3; The plasma treatment in A3 is performed at a power of 70-80 W, for a duration of 50-60 seconds, in an atmosphere of argon and oxygen mixed gas (argon flow rate of 15 L / h, oxygen flow rate of 5 L / h); During the electrospinning process described in A3, the temperature is 25-30°C, the relative humidity is 40%-50%, the voltage is 15 kV, the needle is 15 cm away from the receiving plate, the flow rate of the spinning solution is 0.7-0.9 mL / h, and the moving speed of the etched fiber is 4-5 cm / s; The mass ratio of deionized water, aqueous polyurethane, chitosan quaternary ammonium salt, dioctyl terephthalate, graphene nanosheets, and composite fibers in A4 is 130-186:140-200:14-20:22.5-32:1-2:14-20; The irradiation treatment in A4 is performed at a temperature of 45-55° C., a power of 100-150 W, and a duration of 3-5 minutes.

[0011] Preferably, the mass ratio of deionized water, silane coupling agent KH-560, glacial acetic acid, nano-alumina, carboxyl nitrile rubber, and silane coupling agent KH-570 ethanol solution in A5 is 9-10: 2-2.2: 0.5-0.6: 15-17: 75-83: 100-110; After grinding as described in A5, D90 is 0.5-2 μm; The mass fraction of the silane coupling agent KH-570 ethanol solution described in A5 is 0.5%; The infrared irradiation described in A5 has a wavelength of 3-5 μm, a temperature of 100° C., and a duration of 3-5 minutes.

[0012] A method for preparing wear-resistant and puncture-resistant nitrile gloves comprises the following steps: S1: Immerse the ceramic hand mold in a sodium hydroxide solution for 2-5 minutes, rinse with deionized water 3-5 times, dry at 75-80°C for 10-30 minutes, immerse in an ethanol-containing calcium nitrate aqueous solution for 3-5 seconds, and then dry at 65-70°C for 2-5 minutes to obtain a pretreated hand mold; S2: Immerse the pretreated hand mold in the composite latex for 5-8 seconds and then remove it. After the film is formed, dry it at 45-50°C for 1-3 minutes. Then, immerse the fingertip 2-3 cm away for a second time for 2-3 seconds, then soak it in deionized water at 55-60°C for 5-10 minutes, and finally dry it with forced air at 75-80°C for 5-7 minutes to obtain a crude glove. S3: Use a crimping machine to roll up the opening of the rough glove by 2-3 mm, then perform vulcanization treatment, chlorine washing, neutralization, water washing, drying and demoulding in sequence to obtain wear-resistant and puncture-resistant nitrile gloves.

[0013] Preferably, the mass fraction of the sodium hydroxide solution in S1 is 5%, and the temperature is 55-60°C; The mass fraction of the calcium nitrate aqueous solution in S1 is 10%-15%, and the content of ethanol is 3%; The speed of the lifting in S2 is 8-10 cm / min; The thickness of the adhesive film in S2 is 0.08-0.12 mm.

[0014] Preferably, the vulcanization treatment in S3 is: first vulcanizing at 110-120°C for 15-20 minutes, then vulcanizing at 98-100°C for 20-30 minutes, and then water cooling to 20-40°C; The chlorine washing in S3 is: immersing in an active chlorine aqueous solution with a concentration of 300-500 mg / L for 30-40 seconds; The neutralization in S3 is: neutralizing with a sodium bisulfate aqueous solution to a pH of 6-7.

[0015] Beneficial effects of the present invention: The present invention provides a wear-resistant and puncture-resistant nitrile glove and a preparation method thereof. The present invention effectively improves the anti-static, wear-resistant and puncture-resistant capabilities of the nitrile glove through the following method.

[0016] (1) The nano-diamonds and nano-alumina in the synergistic fibers of the present invention can resist external wear during friction and reduce the direct loss of the matrix material; after etching and plasma treatment, the surface roughness of the basalt fiber increases, and the bonding force with the spinning solution and the coating layer is enhanced, which can act as a skeleton to bear the friction stress and reduce the wear of the film caused by local stress concentration; the structure of carboxylated single-walled carbon nanotubes and graphene can form a "lubrication-blocking" effect during friction, which not only reduces the friction coefficient but also prevents the expansion of wear cracks; the silane coupling agent and plasma treatment optimize the interface bonding between the fiber and the carboxylated nitrile latex matrix, avoid the separation of the fiber and the film to form wear debris, and further improve the wear resistance.

[0017] (2) The hard particles such as nanodiamonds and nanoalumina in the synergistic fibers of the present invention can directly resist the penetration of the puncturing object, and hinder the deformation and penetration caused by the tip of the puncturing object through high hardness; basalt fiber acts as a continuous phase reinforcement to disperse the local impact force during puncture and reduce the local damage of the puncturing object to the film; the high mechanical properties of carboxylated single-walled carbon nanotubes and graphene can form a "bridge" during the puncture process, preventing the crack from extending from the puncture point to the surrounding area and delaying the rupture of the film; the nitrile latex of the electrospinning layer and the water-based polyurethane of the coating layer have a certain elasticity, which can absorb part of the puncture energy through deformation, and form a "hard-tough" composite structure with the rigid components to improve the puncture resistance.

[0018] (3) The carboxylated single-walled carbon nanotubes and graphene nanosheets in the synergistic fiber of the present invention form a continuous conductive network during the electrospinning and coating process, which makes the glove material have a certain conductivity; plasma treatment introduces polar groups on the surface of basalt fiber, enhances the binding force with carbon nanotubes and graphene, reduces the interface resistance, and facilitates the rapid release of charge through the fiber network; the dispersion of conductive components can reduce the surface resistance of the glove material and reduce the accumulation of static electricity on the surface, thereby improving the anti-static performance.

[0019] (4) The nano zinc oxide in the synergistic fiber of the present invention can release zinc ions to destroy bacterial cell membranes and inhibit bacterial enzyme activity; chitosan quaternary ammonium salt can adsorb negatively charged bacteria through electrostatic action, destroy their cell walls, and cooperate with nano zinc oxide to improve the antibacterial efficiency; nano zinc oxide and chitosan quaternary ammonium salt are fixed in the synergistic fiber through coating and interface bonding, and can slowly release or continuously exert antibacterial effects through contact, thereby extending the antibacterial effect of the gloves.

[0020] (5) The carboxyl nitrile rubber in the synergistic fiber of the present invention has a similar chemical structure to the carboxyl nitrile latex matrix of the gloves, has good compatibility, and is not easily degraded due to interface separation at low temperatures; elastic components such as nitrile latex and water-based polyurethane can reduce the low-temperature brittleness of the film, and cooperate with the reinforcing effect of the synergistic fiber to maintain the tensile toughness at low temperatures; the material is prone to failure due to brittle fracture at low temperatures, while the high toughness of carbon nanotubes and graphene can prevent crack propagation through "crack bridging" and "pull-out effect", reducing brittle fracture at low temperatures; silane coupling agent treatment enhances the interfacial bonding force between the synergistic fiber and the matrix, avoids the "debonding-fracture" problem caused by the decrease in interfacial bonding force at low temperatures, and maintains mechanical stability at low temperatures.

[0021] Therefore, the wear-resistant and puncture-resistant nitrile gloves prepared by the present invention have excellent wear resistance, puncture resistance, antistatic properties, antibacterial properties and low-temperature resistance, as well as broader application prospects. DETAILED DESCRIPTION

[0022] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0023] Unless otherwise specified, some of the raw materials used in the following examples and comparative examples of the present invention are as follows: Basalt fiber (diameter 5-7 μm, aspect ratio 5:1); nitrile latex (solid content 43.5%) was purchased from Xingtianwai Chemical (Shanghai) Co., Ltd.; polyvinyl pyrrolidone was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S30268; water-based polyurethane was purchased from Shanghai Mairui Biochemical Technology Co., Ltd., item number: M90109; graphene nanosheets were purchased from Xi'an Ruixi Biotechnology Co., Ltd., item number: 23801; carboxyl nitrile rubber was purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd., item number: 5541254; sodium polycarboxylate was purchased from Nantong Deyi Chemical Co., Ltd., model: DY-YL-330; carboxyl nitrile latex (solid content 44%) was purchased from Hubei Hongfuda Biotechnology Co., Ltd.

[0024] Example 1: A method for preparing wear-resistant and puncture-resistant nitrile gloves is as follows: S1: 5 g of ammonium bifluoride and 3 g of citric acid were added to 100 mL of deionized water and stirred for 10 min. Then, 20 g of basalt fiber was added and ultrasonically dispersed at 45 °C for 30 min. The fiber was then centrifuged and washed five times with deionized water and dried at 55 °C to obtain the etched fiber. S2: 30 g of anhydrous ethanol, 1 g of carboxylated single-walled carbon nanotubes, and 0.05 g of sodium dodecylbenzenesulfonate were added to 30 g of deionized water and ultrasonically dispersed for 30 min. Then, 3 g of nano-zinc oxide and 2 g of nano-diamonds were added and ultrasonically dispersed for 30 min. Then, 0.188 g of 3-cyanopropyltrimethoxysilane was added and stirred at 55°C for 2 h. Finally, 5 g of nitrile latex and 0.2 g of polyvinyl pyrrolidone were added and stirred for 10 min to obtain a spinning solution. S3: The etched fiber was placed in an atmospheric pressure plasma treatment apparatus, and an argon / oxygen mixed gas (argon flow rate of 15 L / h, oxygen flow rate of 5 L / h) was introduced and subjected to a plasma treatment at a power of 70 W for 50 seconds. Afterwards, the etched fiber was electrospun at a moving speed of 4 cm / s using a spinning solution at a flow rate of 0.7 mL / h at 25°C, a relative humidity of 40%, a voltage of 15 kV, and a needle distance of 15 cm from the receiving plate. The composite fiber was then vacuum dried at 75°C for 1 hour to obtain a composite fiber. S4: 140 g of aqueous polyurethane, 14 g of chitosan quaternary ammonium salt, 22.5 g of dioctyl terephthalate, and 1 g of graphene nanosheets were added to 130 g of deionized water and the pH was adjusted to 6.5 with a 1% acetic acid aqueous solution, and then treated at 2500 r / min for 30 min. Then, 14 g of composite fiber was immersed in it, soaked for 8 min, taken out, and placed in a microwave reactor for irradiation at 45 ° C for 3 min with a power of 100 W. Finally, it was dried at 55 ° C for 1 h to obtain a coated fiber; S5: Add 2g of silane coupling agent KH-560 and 0.5g of glacial acetic acid to 9g of deionized water and stir for 10min. Then add 15g of nano-alumina and 75g of carboxyl nitrile rubber and stir at 2000r / min for 20min. Grind until D90 is 0.5μm and spray it on the surface of the coated fiber to form a coating with a thickness of 3μm. Then place it in an infrared curing oven for 3min with a wavelength of 3μm and a temperature of 100℃, then keep it at 60℃ for 1h, and finally immerse it in 100g of 0.5% silane coupling agent KH-570 ethanol solution for 10min. After draining, dry it at 75℃ for 30min to obtain synergistic fiber. S6: Add 3 g of sulfur, 4 g of titanium dioxide, 1 g of zinc oxide, and 0.2 g of sodium polycarboxylate to 5 g of deionized water and ball-mill until the D90 is 0.5 μm to obtain a mixed dispersion; S7: Add 0.4 g of accelerator ZDBC and 0.2 g of accelerator ZDEC to 5.4 g of deionized water at 45°C and stir for 20 min to obtain an accelerator solution; S8: 80 g of carboxyl nitrile latex was stirred at 50 r / min at 25° C. for 8 h, and then 13 g of the mixed dispersion, 0.5 g of antioxidant RD, 6 g of accelerator solution, and 6 g of synergistic fiber were added in sequence while stirring, and the pH was adjusted to 8.5. After stirring for 2 h, the mixture was aged at 25° C. for 8 h to obtain a composite latex; S9: Immerse the ceramic hand mold in a 5% sodium hydroxide solution at 55°C for 2 minutes, rinse with deionized water three times, dry at 75°C for 10 minutes, immerse in a 10% calcium nitrate aqueous solution containing 3% ethanol for 3 seconds, and then dry at 65°C for 2 minutes to obtain a pretreated hand mold; S10: The pretreated hand mold was immersed in the composite latex at 25°C for 5 seconds and then withdrawn at 8 cm / min to form a 0.08 mm thick film. The film was then dried with air at 45°C for 1 minute. The 2 cm portion at the fingertip was then immersed again for 2 seconds. The hand mold was then immersed in deionized water at 55°C for 5 minutes. Finally, the hand mold was dried with air at 75°C for 5 minutes to obtain a crude glove. S11: Use a crimping machine to roll up the opening of the crude glove by 2 mm, then first vulcanize it at 110°C for 15 minutes, then cool it to 98°C at a rate of 5°C / min and vulcanize it at 98°C for 20 minutes, then water-cool it to 20°C, and finally immerse it in a 300 mg / L active chlorine aqueous solution for 30 seconds, then neutralize it in a sodium bisulfate aqueous solution to a pH of 6, wash it with water 5 times, coat it with corn starch and demold it to obtain wear-resistant and puncture-resistant nitrile gloves.

[0025] Example 2: A method for preparing wear-resistant and puncture-resistant nitrile gloves is as follows: S1: 5.5 g of ammonium bifluoride and 3.3 g of citric acid were added to 110 mL of deionized water and stirred for 15 min. Then, 22.5 g of basalt fiber was added and ultrasonically dispersed at 48 °C for 40 min. The fiber was then centrifuged and washed with deionized water six times and dried at 58 °C to obtain the etched fiber. S2: 37.5 g of anhydrous ethanol, 1.3 g of carboxylated single-walled carbon nanotubes, and 0.06 g of sodium dodecylbenzenesulfonate were added to 37.5 g of deionized water and ultrasonically dispersed for 40 min. Then, 3.8 g of nano-zinc oxide and 2.5 g of nano-diamonds were added and ultrasonically dispersed for 40 min. Then, 0.23 g of 3-cyanopropyltrimethoxysilane was added and stirred at 58°C for 2.5 h. Finally, 6.3 g of nitrile latex and 0.25 g of polyvinyl pyrrolidone were added and stirred for 15 min to obtain a spinning solution. S3: The etched fiber was placed in an atmospheric pressure plasma treatment apparatus, and an argon / oxygen mixed gas (argon flow rate of 15 L / h, oxygen flow rate of 5 L / h) was introduced and subjected to a plasma treatment at a power of 75 W for 55 seconds. Afterwards, the etched fiber was electrospun at a moving speed of 4.5 cm / s using a spinning solution at a flow rate of 0.8 mL / h at 28°C, a relative humidity of 45%, a voltage of 15 kV, and a needle distance of 15 cm from the receiving plate. The composite fiber was then vacuum dried at 78°C for 1.5 hours to obtain a composite fiber. S4: 170 g of aqueous polyurethane, 17 g of chitosan quaternary ammonium salt, 27.2 g of dioctyl terephthalate, and 1.5 g of graphene nanosheets were added to 158 g of deionized water and the pH was adjusted to 7 with a 1% acetic acid aqueous solution and treated at 2800 rpm for 35 min. 17 g of composite fiber was then immersed in the water and soaked for 9 min. The composite fiber was then taken out and placed in a microwave reactor for irradiation at 50 ° C for 4 min with a power of 130 W. Finally, the coated fiber was dried at 58 ° C for 1.5 h. S5: Add 2.1g of silane coupling agent KH-560 and 0.55g of glacial acetic acid to 9.5g of deionized water and stir for 15min. Then add 16g of nano-alumina and 79g of carboxyl nitrile rubber and stir at 2100r / min for 25min. Grind until D90 is 1μm and spray it on the surface of the coated fiber to form a coating with a thickness of 4μm. Then place it in an infrared curing oven for 4min with a wavelength of 4μm and a temperature of 100℃, then keep it at 70℃ for 1.5h, and finally immerse it in 105g of 0.5% silane coupling agent KH-570 ethanol solution for 13min. After draining, dry it at 78℃ for 40min to obtain a synergistic fiber. S6: Add 3.5 g of sulfur, 3 g of titanium dioxide, 3 g of phthalocyanine blue, and 0.3 g of sodium polycarboxylate to 6 g of deionized water and ball-mill until the D90 is 0.1 μm to obtain a mixed dispersion; S7: Add 0.6 g of accelerator ZDBC and 0.3 g of accelerator ZDEC to 8.1 g of deionized water at 48°C and stir for 30 min to obtain an accelerator solution; S8: 85 g of carboxylated nitrile latex was stirred at 60 rpm at 28° C. for 9 h, and then 15.5 g of the mixed dispersion, 0.8 g of antioxidant RD, 9 g of accelerator solution, and 7 g of synergistic fiber were added in sequence while stirring, and the pH was adjusted to 9. After stirring for 3 h, the mixture was aged at 28° C. for 9 h to obtain a composite latex. S9: Immerse the ceramic hand mold in a 5% sodium hydroxide solution at 58°C for 3 minutes, rinse with deionized water four times, dry at 78°C for 20 minutes, immerse in a 13% calcium nitrate aqueous solution containing 3% ethanol for 4 seconds, and then dry at 68°C for 4 minutes to obtain a pretreated hand mold; S10: The pretreated hand mold was immersed in the composite latex at 27°C for 7 seconds and then withdrawn at 9 cm / min to form a 0.1 mm thick film. The film was then dried at 48°C with air for 2 minutes. The 2.5 cm portion of the fingertip was then immersed again for 2.5 seconds. The hand mold was then immersed in deionized water at 58°C for 8 minutes. Finally, the hand mold was dried at 78°C with air for 6 minutes to obtain a crude glove. S11: Use a crimping machine to roll up the opening of the crude glove by 2.5 mm, then first vulcanize it at 115°C for 18 minutes, then cool it to 99°C at a rate of 5°C / min and vulcanize it at 99°C for 25 minutes, then water-cool it to 30°C, and finally immerse it in a 400 mg / L active chlorine aqueous solution for 35 seconds, then neutralize it in a sodium bisulfate aqueous solution to a pH of 6.5, wash it with water 8 times, coat it with corn starch and demold it to obtain wear-resistant and puncture-resistant nitrile gloves.

[0026] Example 3: A method for preparing wear-resistant and puncture-resistant nitrile gloves is as follows: S1: 6 g of ammonium bifluoride and 3.5 g of citric acid were added to 120 mL of deionized water and stirred for 20 min. Then, 25 g of basalt fiber was added and ultrasonically dispersed at 50 °C for 50 min. The fiber was then centrifuged and washed seven times with deionized water and dried at 60 °C to obtain the etched fiber. S2: 45 g of anhydrous ethanol, 1.5 g of carboxylated single-walled carbon nanotubes, and 0.07 g of sodium dodecylbenzenesulfonate were added to 45 g of deionized water and ultrasonically dispersed for 50 min. Then, 4.5 g of nano-zinc oxide and 3 g of nano-diamonds were added and ultrasonically dispersed for 50 min. Then, 0.28 g of 3-cyanopropyltrimethoxysilane was added and stirred at 60°C for 3 h. Finally, 7.5 g of nitrile latex and 0.3 g of polyvinylpyrrolidone were added and stirred for 20 min to obtain a spinning solution. S3: The etched fiber was placed in an atmospheric pressure plasma treatment apparatus, and an argon / oxygen mixed gas (argon flow rate of 15 L / h, oxygen flow rate of 5 L / h) was introduced and subjected to a plasma treatment at a power of 80 W for 60 seconds. Afterwards, the etched fiber was electrospun at a moving speed of 5 cm / s using a spinning solution at a flow rate of 0.9 mL / h at 30°C, a relative humidity of 50%, a voltage of 15 kV, and a needle distance of 15 cm from the receiving plate. The composite fiber was then vacuum dried at 80°C for 2 hours to obtain a composite fiber. S4: 200 g of aqueous polyurethane, 20 g of chitosan quaternary ammonium salt, 32 g of dioctyl terephthalate, and 2 g of graphene nanosheets were added to 186 g of deionized water and the pH was adjusted to 7.5 with a 1% acetic acid aqueous solution and then treated at 3000 r / min for 40 min. Then, 20 g of composite fiber was immersed in it, soaked for 10 min, taken out and placed in a microwave reactor for 5 min at a power of 150 W at 55 ° C. Finally, it was dried with air at 60 ° C for 2 h to obtain a coated fiber; S5: Add 2.2g of silane coupling agent KH-560 and 0.6g of glacial acetic acid to 10g of deionized water and stir for 20min, then add 17g of nano-alumina and 83g of carboxyl nitrile rubber and stir at 2200r / min for 30min, grind to D90 of 2μm and spray it on the surface of the coated fiber to form a coating with a thickness of 5μm. Then place it in an infrared curing oven for 5min with a wavelength of 5μm and a temperature of 100℃, then keep it at 80℃ for 2h, and finally immerse it in 110g of 0.5% silane coupling agent KH-570 ethanol solution for 15min, drain it and dry it at 80℃ for 50min to obtain a synergistic fiber; S6: Add 4 g of sulfur, 5 g of titanium dioxide, 2 g of pearlescent pigment, and 0.4 g of sodium polycarboxylate to 7 g of deionized water and ball-mill until the D90 is 2 μm to obtain a mixed dispersion; S7: Add 0.8 g of accelerator ZDBC and 0.4 g of accelerator ZDEC to 10.8 g of deionized water at 50°C and stir for 40 min to obtain an accelerator solution; S8: 90 g of carboxyl nitrile latex was stirred at 70 rpm at 30°C for 10 h, and then 18 g of the mixed dispersion, 1.1 g of antioxidant RD, 12 g of accelerator solution, and 8 g of synergistic fiber were added in sequence while stirring, and the pH was adjusted to 9.5. After stirring for 4 h, the mixture was aged at 30°C for 10 h to obtain a composite latex; S9: Immerse the ceramic hand mold in a 5% sodium hydroxide solution at 60°C for 5 minutes, rinse with deionized water 5 times, dry at 80°C for 30 minutes, immerse in a 15% calcium nitrate aqueous solution containing 3% ethanol for 5 seconds, and then dry at 70°C for 5 minutes to obtain a pretreated hand mold; S10: The pretreated hand mold was immersed in a 30°C composite latex for 8 seconds and then withdrawn at a speed of 10 cm / min to form a 0.12 mm thick film. The film was then dried at 50°C with air for 3 minutes. The 3 cm portion at the fingertip was then immersed again for 3 seconds. The hand mold was then immersed in deionized water at 60°C for 10 minutes. Finally, the hand mold was dried at 80°C with air for 7 minutes to obtain a crude glove. S11: Use a crimping machine to roll up the opening of the crude glove by 3 mm, then first vulcanize it at 120°C for 20 minutes, then cool it to 100°C at a rate of 5°C / min and vulcanize it at 100°C for 30 minutes, then water-cool it to 40°C, and finally immerse it in a 500 mg / L active chlorine aqueous solution for 40 seconds, then neutralize it in a sodium bisulfate aqueous solution to a pH of 7, wash it with water 10 times, coat it with corn starch and demold it to obtain wear-resistant and puncture-resistant nitrile gloves.

[0027] Comparative Example 1: Compared with Example 1, this comparative example only does not add "carboxylated single-walled carbon nanotubes" during the preparation of S1. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0028] Comparative Example 2: Compared with Example 1, this comparative example only does not add "nano zinc oxide" during the preparation process of S2. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0029] Comparative Example 3: Compared with Example 1, this comparative example only does not add "nanodiamond" during the preparation process of S2. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0030] Comparative Example 4: Compared with Example 1, this comparative example only replaces the "etched fiber" added in the preparation process of S3 with "basalt fiber". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0031] Comparative Example 5: Compared with Example 1, this comparative example only does not add "graphene nanosheets" during the preparation process of S4. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0032] Comparative Example 6: Compared with Example 1, this comparative example only replaces the "composite fiber" added in the preparation process of S4 with "etched fiber", and the remaining steps and parameters are the same. This comparative example will not be repeated, and finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0033] Comparative Example 7: Compared with Example 1, this comparative example only does not add "nano-alumina" during the preparation of S5. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0034] Comparative Example 8: Compared with Example 1, this comparative example only replaces the "coated fiber" added in the preparation process of S5 with "composite fiber". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0035] Comparative Example 9: Compared with Example 1, this comparative example only replaces the "synergistic fiber" added in the preparation process of S8 with "coated fiber", and the remaining steps and parameters are the same. This comparative example will not be repeated, and finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0036] Comparative Example 10: Compared with Example 1, this comparative example only does not add "synergistic fiber" during the preparation process of S8. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, wear-resistant and puncture-resistant nitrile gloves are obtained.

[0037] Performance testing: Determination of wear resistance: With reference to GB / T 1689-2014 "Determination of wear resistance of vulcanized rubber (using Akron abrasion tester)", the wear-resistant and puncture-resistant nitrile gloves prepared in Examples 1 to 3 and Comparative Examples 1 to 10 of the present invention were measured after being rubbed for 1.61 km with a 100-mesh silicon carbide grinding wheel under a constant load of 26.5 N (cm 3 ), the test results are shown in Table 1; Determination of puncture resistance: With reference to GB / T 21867-2008 "General Technical Requirements for Gloves", the puncture resistance (N) of the palm portion of the wear-resistant and puncture-resistant nitrile gloves prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 10 was measured at a puncture speed of 100 mm / min. The test results are shown in Table 1. Determination of antistatic properties: With reference to GB / T 1410-2006 "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials", the surface resistivity (Ω) of the wear-resistant and puncture-resistant nitrile gloves prepared in Examples 1 to 3 and Comparative Examples 1 to 10 of the present invention was measured. The test results are shown in Table 1. Determination of antibacterial activity: With reference to GB 15979-2024 "Hygiene Requirements for Disposable Sanitary Products", the antibacterial rates (%) of the wear-resistant and puncture-resistant nitrile gloves prepared in Examples 1 to 3 and Comparative Examples 1 to 10 of the present invention were measured. The test results are shown in Table 1. Determination of low temperature resistance: With reference to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", the elongation at break (%) of the palm portion of the wear-resistant and puncture-resistant nitrile gloves prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 10 was measured at a tensile speed of 500 mm / min at -40°C (measured at -40°C after being stored at -40°C for 24 hours). The test results are shown in Table 1.

[0038] Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-10 project <![CDATA[Wear resistance / cm 3 > Puncture resistance / N Antistatic property / Ω Antibacterial activity / % Low temperature resistance / % Example 1 0.04 87.7 <![CDATA[1.5×10 6 ]]> 99.9 349 Example 2 0.03 88.1 <![CDATA[1.3×10 6 ]]> 99.9 355 Example 3 0.04 87.5 <![CDATA[1.6×10 6 ]]> 99.9 347 Comparative Example 1 0.09 79.8 <![CDATA[8.5×10 8 ]]> 99.8 301 Comparative Example 2 0.05 86.2 <![CDATA[1.7×10 6 ]]> 87.4 342 Comparative Example 3 0.07 80.8 <![CDATA[1.6×10 6 ]]> 99.9 345 Comparative Example 4 0.10 73.9 <![CDATA[1.9×10 7 ]]> 99.7 338 Comparative Example 5 0.08 80.1 <![CDATA[5.8×10 8 ]]> 99.9 306 Comparative Example 6 0.17 60.0 <![CDATA[9.1×10 8 ]]> 85.6 283 Comparative Example 7 0.07 80.9 <![CDATA[1.5×10 6 ]]> 99.8 346 Comparative Example 8 0.15 63.2 <![CDATA[1.8×10 6 ]]> 67.8 172 Comparative Example 9 0.14 63.8 <![CDATA[2.3×10 7 ]]> 99.5 169 Comparative Example 10 0.25 39.1 <![CDATA[9.5×10 11 ]]> 45.2 66 Data Analysis: As can be seen from Table 1, the wear-resistant and puncture-resistant nitrile gloves prepared in the embodiment of the present invention have excellent wear resistance, puncture resistance, antistatic properties, antibacterial properties and low temperature resistance.

[0039] The above is a detailed description of an embodiment of the present invention. However, the content described is only a preferred embodiment of the present invention and should not be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A wear-resistant and puncture-resistant nitrile glove, characterized in that: The nitrile gloves are made from composite rubber latex; The composite latex comprises the following raw materials in parts by weight: 80-90 parts of carboxyl nitrile latex, 13-18 parts of mixed dispersion, 0.5-1.1 parts of antioxidant RD, 6-12 parts of accelerator solution, and 6-8 parts of synergistic fiber; The mixed dispersion is prepared from deionized water, sulfur, pigment, and sodium polycarboxylate; The synergistic fiber is prepared by electrostatically spinning basalt fibers with spinning solution after etching, and then sequentially coating with graphene nanosheets doped with polyurethane and nanoalumina doped with carboxylated nitrile rubber. The spinning solution includes carboxylated single-walled carbon nanotubes, sodium dodecylbenzenesulfonate, nano zinc oxide, nano diamond, γ-cyanopropyltrimethoxysilane, nitrile latex and polyvinyl pyrrolidone.

2. The wear-resistant and puncture-resistant nitrile gloves according to claim 1, characterized in that: The preparation method of the composite latex is as follows: The carboxyl nitrile latex is stirred for 8-10 hours, and then the mixed dispersion, antioxidant RD, accelerator solution, and synergistic fiber are added in sequence while stirring and the pH is adjusted to 8.5-9.

5. After stirring for 2-4 hours, the mixture is matured at 25-30°C for 8-10 hours to obtain a composite latex.

3. The wear-resistant and puncture-resistant nitrile gloves according to claim 1, characterized in that: The preparation method of the mixed dispersion is as follows: sulfur, pigment, and sodium polycarboxylate are added to deionized water and ball-milled to obtain a mixed dispersion; The mass ratio of the deionized water, sulfur, pigment, and sodium polycarboxylate is 5-7:3-4:5-7:0.2-0.4; The pigment is a composition of titanium dioxide and any one of zinc oxide, phthalocyanine blue and pearlescent pigment.

4. The wear-resistant and puncture-resistant nitrile gloves according to claim 1, characterized in that: The preparation method of the accelerator solution is as follows: Add accelerator ZDBC and accelerator ZDEC to deionized water and stir well to obtain an accelerator solution; The mass ratio of the deionized water, the accelerator ZDBC, and the accelerator ZDEC is 5.4-10.8:0.4-0.8:0.2-0.

4.

5. The wear-resistant and puncture-resistant nitrile gloves according to claim 1, characterized in that: The preparation method of the synergistic fiber is as follows: A1: Add ammonium bifluoride and citric acid to deionized water and mix well. Then add basalt fiber and sonicate. Then centrifuge and dry to obtain etched fiber. A2: Anhydrous ethanol, carboxylated single-walled carbon nanotubes, and sodium dodecylbenzenesulfonate were added to deionized water and sonicated. Nano-zinc oxide and nano-diamonds were then added and sonicated. γ-cyanopropyltrimethoxysilane was then added and stirred for 2-3 hours. Finally, nitrile latex and polyvinyl pyrrolidone were added and stirred to obtain a spinning solution. A3: Plasma-treating the etched fiber and then electrospinning it with a spinning solution, followed by drying to obtain a composite fiber; A4: Add waterborne polyurethane, chitosan quaternary ammonium salt, dioctyl terephthalate, and graphene nanosheets to deionized water, adjust the pH, and stir. Then, immerse the composite fiber in the water, remove the fiber, irradiate it, and dry it to obtain a coated fiber. A5: Add silane coupling agent KH-560 and glacial acetic acid to deionized water and stir well. Then add nano-alumina and carboxyl nitrile rubber and stir well. Grind and spray on the surface of the coated fiber, then irradiate with infrared light and keep warm at 60-80℃ for 1-2h. Finally, immerse in silane coupling agent KH-570 ethanol solution, drain and dry to obtain synergistic fiber.

6. The wear-resistant and puncture-resistant nitrile gloves according to claim 5, characterized in that: The mass ratio of deionized water, ammonium bifluoride, citric acid, and basalt fiber in A1 is 100-120:5-6:3-3.5:20-25; The mass ratio of deionized water, anhydrous ethanol, carboxylated single-walled carbon nanotubes, sodium dodecylbenzenesulfonate, nano-zinc oxide, nano-diamond, γ-cyanopropyltrimethoxysilane, nitrile latex, and polyvinyl pyrrolidone in A2 is 30-45:30-45:1-1.5:0.05-0.07:3-4.5:2-3:0.18-0.28:5-7.5:0.2-0.3; The plasma treatment in A3 has a power of 70-80 W, a duration of 50-60 s, and a treatment atmosphere of a mixture of argon and oxygen; During the electrospinning process described in A3, the temperature is 25-30°C, the relative humidity is 40%-50%, the voltage is 15 kV, the needle is 15 cm away from the receiving plate, the flow rate of the spinning solution is 0.7-0.9 mL / h, and the moving speed of the etched fiber is 4-5 cm / s; The mass ratio of deionized water, aqueous polyurethane, chitosan quaternary ammonium salt, dioctyl terephthalate, graphene nanosheets, and composite fibers in A4 is 130-186:140-200:14-20:22.5-32:1-2:14-20; The pH value after adjusting the pH in A4 is 6.5-7.5; The stirring treatment in A4 is as follows: stirring at 2500-3000 r / min for 30-40 min; The irradiation temperature in A4 is 45-55° C., the power is 100-150 W, and the duration is 3-5 minutes.

7. The wear-resistant and puncture-resistant nitrile gloves according to claim 5, characterized in that: The mass ratio of deionized water, silane coupling agent KH-560, glacial acetic acid, nano-alumina, carboxyl nitrile rubber, and silane coupling agent KH-570 ethanol solution in A5 is 9-10:2-2.2:0.5-0.6:15-17:75-83:100-110; The infrared irradiation described in A5 has a wavelength of 3-5 μm, a temperature of 100° C., and a duration of 3-5 minutes.

8. A method for preparing the wear-resistant and puncture-resistant nitrile gloves according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: The ceramic hand mold is immersed in a sodium hydroxide solution for cleaning, then rinsed with deionized water, dried, and immersed in a calcium nitrate aqueous solution containing ethanol, and then taken out and dried to obtain a pretreated hand mold; S2: The pretreated hand mold is immersed in the composite latex and then taken out. After the film is formed, it is dried at 45-50°C for 1-3 minutes. Then, the fingertip part is immersed in deionized water at 55-60°C for a second time, and finally taken out and dried to obtain a crude glove; S3: Roll up the opening of the crude glove by 2-3 mm, then perform vulcanization treatment, chlorine washing, neutralization, water washing, drying and demoulding in sequence to obtain wear-resistant and puncture-resistant nitrile gloves.

9. The method for preparing wear-resistant and puncture-resistant nitrile gloves according to claim 8, characterized in that: The mass fraction of the sodium hydroxide solution in S1 is 5%, and the temperature is 55-60°C; The mass fraction of the calcium nitrate aqueous solution in S1 is 10%-15%, and the content of ethanol is 3%; The thickness of the adhesive film in S2 is 0.08-0.12 mm.

10. The method for preparing wear-resistant and puncture-resistant nitrile gloves according to claim 8, characterized in that: The vulcanization treatment in S3 is: first vulcanizing at 110-120°C for 15-20 minutes, then vulcanizing at 98-100°C for 20-30 minutes, and then water cooling to 20-40°C; The chlorine washing in S3 is: immersing in an active chlorine aqueous solution with a concentration of 300-500 mg / L for 30-40 seconds; The neutralization in S3 is: neutralizing with a sodium bisulfate aqueous solution to a pH of 6-7.

Citation Information

Patent Citations

  • White graphene antibacterial functional glove and preparation method thereof

    CN114128944A

  • Conductive butyronitrile impregnated glove and preparation method thereof

    CN118459865A

  • Green low-cost sugar-based multifunctional carbon fiber and preparation method thereof

    CN119843392A

  • Cut-resistant protective glove and manufacturing method therefor

    WO2023173502A1

  • Graphene flame-retardant glove and preparation method therefor

    WO2024124614A1